2019
DOI: 10.1248/cpb.c18-00806
|View full text |Cite
|
Sign up to set email alerts
|

YiQi Tongluo Granule against Cerebral Ischemia/Reperfusion Injury in Rats by Freezing GluN2B and CaMK II through NMDAR/ERK1/2 Signaling

Abstract: Yiqi Tongluo Granule (YQTL) is a kind of proprietary Chinese medicine, manufactured by ChinaShineway Pharmaceutical Group Ltd., under the authority of China Food and Drug Administration (CFDA) treating cardiovascular and cerebrovascular diseases such as ischemic stroke in China, however the underlying mechanism of YQTL on treating ischemic stroke has not been revealed. This study is aimed to evaluate the protective effect of YQTL on cerebral ischemia/reperfusion (I/R) injury and inquire into its underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In recent years, excitatory amino acid (EAA) toxicity and subsequent calcium overload have attracted attention in cerebral ischemia and VaD injury [ 33 ]. Acute ischemic injury caused increased permeability of the neuronal cell membrane to calcium ions, resulting in intracellular Ca 2+ overload, including severe neuronal apoptosis and destruction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, excitatory amino acid (EAA) toxicity and subsequent calcium overload have attracted attention in cerebral ischemia and VaD injury [ 33 ]. Acute ischemic injury caused increased permeability of the neuronal cell membrane to calcium ions, resulting in intracellular Ca 2+ overload, including severe neuronal apoptosis and destruction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whole experiment was divided into three batches. The first batch comprised 72 healthy male SD rats, randomly divided into six groups with 12 In the second batch, 40 SD rats were randomly divided into four groups of 10 rats each. These were Sham, MCAO, MCAO + Positive drug (0.02 g/kg, Nimodipine 0.02 g/kg) and MCAO + NLXT drug (2.25 g/kg).…”
Section: Grouping and Dosagesmentioning
confidence: 99%
“…The fascia was separated to expose the skull. The location of rCBF was assessed in relation to Bregma: ML: +2.0 mm, AP: +1.0 mm (12). The infarct site in the cortex was considered as the ischemic peripheral area (the depth was within 1 mm of the cerebral cortex, that is, the ischemic penumbra area).…”
Section: Assessment Of Cerebral Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7) Accumulating evidence has shown that traditional Chinese medicine can provide protection against neurological diseases and promote neuronal, axonal, and myelin regeneration. 8,9) It has been reported that Curcuma longa protects the dorsal root ganglia (DRG) and sciatic nerve of rats from crush injury. 10) Curcumin is the main ingredient of curcuma longa, possessing multiple pharmacological activities, such as antiinflammatory, antioxidant, antiviral, and antitumor activities, with low toxicity and minimal adverse effects.…”
Section: Introductionmentioning
confidence: 99%